Subjective concerns regarding the effects of sport-related concussion on long-term brain health among former NFL players: an NFL-LONG study - Walton, S. R.; Kerr, Z. Y.; Mannix, R.; Brett, B. L.; Chandran, A.; DeFreese, J. D.; McCrea, M. A.; Guskiewicz, K. M.; Meehan III, W. P.; Echemendia, R. J. (Sports Medicine, 2022)
Background: Potential links between a history of sport-related concussions and later-life neurobiological and psychological brain health have been studied in former collision-sport athletes. However, empirical studies of how former athletes perceive the future of their brain health as a result of these injuries are missing. Objectives: We aimed to (1) identify the extent to which former National Football League players currently have concerns about their long-term psychological and cognitive functioning as a result of concussions sustained while playing football; (2) examine whether current concerns are different than concerns they had while playing football; (3) examine the relationship between current brain health concerns and self-reported concussion history (SR-CHx); and (4) explore other important factors associated with these concerns. Methods: In this cross-sectional study, former National Football League players with a SR-CHx of one or more concussions (n = 1514; aged mean [standard deviation] = 52.3 [15.7] years) completed a general health questionnaire. Participants reported their lifetime concussion history, as well as both their current concerns and concerns while playing football (i.e., retrospective concerns) regarding the long-term effects of concussions on their memory, thinking skills, and risk of developing chronic traumatic encephalopathy. Current and retrospective concerns were self-reported on a five-point Likert scale. Four concussion history categories were created based on SR-CHx: 1-2 (n = 309); 3-5 (n = 413); 6-9 (n = 356); and 10 + (n = 436) lifetime concussions. Proportions of participants reporting each level of current and retrospective concerns were examined to identify whether concerns presently exist in these former players, and whether their current concerns are different than retrospective concerns. Next, we explored associations between current concerns and SR-CHx. Results: More than one-third of participants reported being currently "extremely concerned" about memory problems (36.9%), thinking skills (37.8%), and developing chronic traumatic encephalopathy (39.5%). In contrast, when asked about concerns while playing, most reported being "not at all concerned" regarding memory = 61.2%, thinking skills = 56.1%, and developing chronic traumatic encephalopathy = 71.2%. Of those who retrospectively endorsed being "not at all" or "slightly" concerned regarding memory (n = 1159/1514), thinking skills (n = 1080/1514), and developing chronic traumatic encephalopathy (n = 1219/1514), approximately half reported being currently "moderately" or "extremely" concerned about those same issues (n = 586/1159; n = 534/1080; n = 619/1219, respectively). Current concerns regarding memory (?216 = 316.61; p < 0.001; V = 0.264), thinking skills (?216 = 333.17; p < 0.001; V = 0.271), and developing chronic traumatic encephalopathy (?216 = 280.85; p < 0.001; V = 0.249) were significantly related to SR-CHx, with more concussions being associated with greater current concerns. Conclusions: Former National Football League players reported significant concerns regarding the potential effects of their prior concussions on long-term brain health, and these concerns are more prevalent now than when they were playing football. Cognitive and mental health concerns are readily identifiable targets for clinical intervention. Clinicians working with former players may wish to explore the extent to which individual players experience these concerns, the nature and depth of these concerns, and the impact of these concerns on the player`s functioning and well-being.